Effect of an educational intervention on public knowledge, attitudes, and intended practices towards diabetes mellitus: A quasi‐experimental study. Issue 9 (16th June 2020) - Alsous, Mervat M.; Odeh, Mohanad; Abdel Jalil, Mariam
Abstract: Aim: To assess the impact of educational workshops on the knowledge, attitudes, and intended practices (KAP) of the general public towards diabetes in Jordan in terms of symptoms, risk factors, complications, and prevention. Methods: A pharmacist led educational intervention and Propensity score matching was carried out for a convenience sample to assess Jordanians pre‐ and post‐knowledge, attitudes,  and practices towards diabetes mellitus (DM) using a validated questionnaire. Results: Among the 357 invited participants, 335 attended the educational workshops (response rate 93.8%). Prior to intervention, participants showed an overall knowledge score of 16.03 ± 4.88. About half of the participants knew that a sedentary lifestyle is a risk factor for getting DM ( n  = 172, 51.3%). Following educational intervention, knowledge scores significantly improved to be 21.36 ± 2.11 ( P value < .001). A similar finding was obtained for attitude scores, where mean attitude scores significantly improved from 2.74 ± 1.94 before intervention to 4.40 ± 1.87 following the workshop ( P value < .001). As for the intended practices, the educational intervention improved the participants' intent to exercise, eat healthy foods, and do annual screening. Conclusions: Participants' knowledge, attitudes, and intended practices improved following a trained pharmacy led educational intervention. These encouraging results highlight the need for continuous national educational interventions about diabetes provided by trained health care professionals such as pharmacists. Future studies are needed to evaluate the impact of improved knowledge and perceptions on actual long‐term practice.